2012
DOI: 10.1097/fpc.0b013e328350012b
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling in K-562 cells under imatinib treatment

Abstract: Our study suggests an association of imatinib treatment, miRNA downregulation and ABCG2 overexpression, possibly contributing to the mechanisms involved in imatinib distribution and response in CML therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…Interaction between miRNA-212-3p and ABCG2 was also demonstrated in an earlier study (Turrini et al, 2012). ABCG2 is an important efflux transporter implicated in chemo-resistance of tumor stem cells (Mo and Zhang, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Interaction between miRNA-212-3p and ABCG2 was also demonstrated in an earlier study (Turrini et al, 2012). ABCG2 is an important efflux transporter implicated in chemo-resistance of tumor stem cells (Mo and Zhang, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…In MCF7 breast cancer cells and in K562 CML cells, miR-212 targets the ABCG2 3′-UTR, resulting in diminished ABCG2 expression and decreased resistance to mitoxantrone or imatinib, respectively [85,86]. In a similar manner, Dong et al [87] found that miR-31 targets the 3′-UTR of the ABCB9 mRNA transcript, causing its downregulation and decreased resistance to cisplatin in non-small-cell lung cancer (NSCLC) cells.…”
Section: Roles Of Mirna Species In Mediating Intrinsic and Acquired Resmentioning
confidence: 99%
“…Some in vitro studies have shown that miR-328 inhibits the expression of BCRP mRNA and protein2829. We previously demonstrated that miR-328 levels negatively correlated with BCRP mRNA and protein expression levels in the human placenta7.…”
Section: Discussionmentioning
confidence: 91%
“…The methylation patterns of several CpG dinucleotides proximal to two C/EBPα-binding sites in the miR-328 5′-flanking region negatively correlated with miR-328 levels, and positively correlated with BCRP protein levels in human placental samples7. Other miRNAs such as miR-519c, miR-520h, and miR-212 also regulate the expression of BCRP2829. Li et al .…”
Section: Discussionmentioning
confidence: 99%